Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1209/epl/i1998-00150-y
|View full text |Cite
|
Sign up to set email alerts
|

Giant electronic stop bands in one-dimensional comblike structures

Abstract: We report the existence of gaps in the band structure of a comblike structure of a one-dimensional electronic waveguide with N dangling side branches grafted at N equidistant sites. These gaps originate both from the periodicity of the system and the resonance states of the grafted branches (which play the role of resonators). The width of the gaps depends on the length of the resonators as well as on the numbers N and N . We stress on the tailoring of widths of the passbands (and hence the stop bands) owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…We consider now circuits made of nano-metric wires and will use a continuous model to describe their electronic properties [186]. The geometry investigated in this work is similar to that studied in Section 2.4 and depicted in Fig.…”
Section: Continuous Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider now circuits made of nano-metric wires and will use a continuous model to describe their electronic properties [186]. The geometry investigated in this work is similar to that studied in Section 2.4 and depicted in Fig.…”
Section: Continuous Modelmentioning
confidence: 99%
“…Because of its fundamental interest and practical importance, electronic transport in onedimensional structures with a wide variety of geometries has been intensely investigated in the recent past. These studies include quantum conductance in one-dimensional mesoscopic rings [173,174], the transmission zeros and poles in quantum wave-guides [175][176][177][178][179], the transmission in coupled quantum wires [180][181][182][183][184], the size-effect on conductance in ballistic quantum wires [185], the electronic stop bands [186][187][188], the electron channel drop tunneling [189][190][191], the localization effects [192], the overlap effects on electron transmission through molecular wires [193][194][195], the transmission through two-dimensional lattices [196], . .…”
Section: Introductionmentioning
confidence: 99%
“…This could be of potential interest for developing nanocircuits that may play the role of reflectors or filters for electrons. In previous publications, 22,23 we proposed a model of onedimensional ͑1D͒ monomode waveguide exhibiting passbands separated by large forbidden bands. The geometry of the model presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the photonic band structure was calculated for electromagnetic waves in the periodic dielectric materials [2,3]. For the energy gap of electron, Akjouj et al [4] reported the existence of giant electronic stop bands in one-dimensional comb-like structures. These gaps originated both from the periodicity of the system and the resonance states of the grafted branches that played the role of resonators.…”
Section: Introductionmentioning
confidence: 99%